The Influence of Marketing Communication and Affiliate Marketing on Product Purchase Intention on Instagram @swulann01 - Yanuar, Melinia; Savitri, Citra; Faddila, Syifa Pramudita (Westscience Press, 2024)
The problem in this study is the decline in the performance of Sri Wulan's Shopee affiliate program in recent months, which is inversely proportional to the Insight profile and Instagram story and even Sri Wulan's followers who continue to increase every month. This study aims to determine how influential and significant the variables of marketing communication and marketing affiliation are on product purchase interest on Sri Wulan's Instagram, where marketing communication here focuses on Shopee affiliate marketing Instagram Sri Wulan as an affiliator in the field of fashion style. The method used in this research is quantitative with the Structural Equation Model (SEM) analysis tool using Smart-PLS software version 4. The sample collection technique in this research uses non-probability sampling, namely purposive sampling using the Slovin formula, so that the sample results are 400 respondents with a Likert scale. Based on the results of hypothesis testing, it is found that there is a significant relationship between marketing communication on buying interest in fashion products, there is also a significant relationship between affiliate marketing on buying interest in fashion products for followers of Sri Wulan's Instagram account (@swulann01).